Development of Communications Identification Matrix of Early Screening for Autism Children - Cahyadi Muhammad; Aqilah Thalsa Syahda; Ediyanto Ediyanto; Junaidi Ahsan Romadlon; Jatiningsiwi Tata Gading (Discourse and Communication for Sustainable Education, 2023)
People with autism show identifiable impediments in three central aspects, namely communication, social interaction, and repetitive and restrictive behavior, which is called the triad of impairments. The communication observation of children with autism is relatively complex, so a specific procedure to identify their communication is required. A specific identification procedures on children’s communication aspect facilitate teachers and parents to provide an optimum alternative program for children with autism. This study aims to identify and develop an identification matrix focusing on the communication aspects of children with autism. This study used development methods and a qualitative approach. For the data validity test, we used data triangulation through interviews with experts. The results of this study are the development of a communication identification matrix as an approach on early detection on autism symptom. Despite the development of the identification matrix related to communication aspects, it is recommended to identify aspects related to social interaction and repetitive and restrictive behaviors according to the triad of impairment. As a highlight, early detection or screening cannot directly label that a child has autism, but early detection can be the first step to identify any developmental issues, and parents can refer the child to a psychologist or doctor for a clinical diagnosis.